1958
DOI: 10.2134/agronj1958.00021962005000060008x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Accumulation in Everglades Forages1

Abstract: Synopsis Oats and Italian ryegrass accumulate large quantities of nitrate but permanent pasture grasses and legumes do not. Oat stems contained more nitrate than leaves. Winter forages following summer clean fallow contained more nitrate than those following weeds. Time of season, daily low temperatures, and variations between daily low and high temperatures also affected nitrate contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 2 publications
2
17
0
Order By: Relevance
“…Differences in reactivities of commercial rocks have long been recognized by superphosphate manufacturers, though only recently has attention been given to the development of a scale of reactivity as a means of classifying phosphate from different sources ( 6 ) . The rates of reaction with acid exhibited by the specimens appeared to be associated more with chemical than with physical characteristics.…”
Section: Literature Citedmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in reactivities of commercial rocks have long been recognized by superphosphate manufacturers, though only recently has attention been given to the development of a scale of reactivity as a means of classifying phosphate from different sources ( 6 ) . The rates of reaction with acid exhibited by the specimens appeared to be associated more with chemical than with physical characteristics.…”
Section: Literature Citedmentioning
confidence: 99%
“…calcium-phosphorus ratio, pore size distribution, and surface area (2,6,9)-as well as estimation of the relative reactivity itself by known techniques: measurement of phosphorus solubility in solutions of neutral ammonium citrate, citric acid, and phosphoric acid (3, 8 ) . calcium-phosphorus ratio, pore size distribution, and surface area (2,6,9)-as well as estimation of the relative reactivity itself by known techniques: measurement of phosphorus solubility in solutions of neutral ammonium citrate, citric acid, and phosphoric acid (3, 8 ) .…”
Section: Scope Of Measurementsmentioning
confidence: 99%
“…(1966) found that the nitrate nitrogen content of pearl millet was greater than in some sudangrass hybrids which, in turn, were generally higher 11^ in nitrate nitrogen than was sudangrass. These workers found that the shorter the remaining stubble the higher was the nitrate nitrogen content of the harvested portion, which is in agreement with results reported by Bennett (195#) Kretschmer (1958) and Harris (1963) showed that cultural practice-3 such as fallowing prior to planting have a decided effect on the nitrate content of the various soil layers, whether successively cropped or cropped after fallow. Tucker et (1961) reported that an acid soil, rather than alkaline, tended to promote nitrate absorption from the soil.…”
Section: Nitrate Toxicitysupporting
confidence: 88%
“…(1966) found that the nitrate nitrogen content of pearl millet was greater than in some sudangrass hybrids which, in turn, were generally higher 11^ in nitrate nitrogen than was sudangrass. These workers found that the shorter the remaining stubble the higher was the nitrate nitrogen content of the harvested portion, which is in agreement with results reported by Bennett (195#), Brady jt (1955)» Shive (1931+)» Crawford et al (1961), Hanway and Englehorn (1958), Hanway (1962), and Kretschmer (1958) Since plants must obtain their nitrates from the soil, it might seem that a positive correlation would exist between plant nitrates and soil nitrates; however, Jones (1966) indi cated that correlation of plant response to soil analyses has been poor since soil nitrate at any given time reflects only the difference between production and utilization. He pointed out that nitrates may be stored in the subsoil of somewhat heavy soils and that this supply, which is usually not measured when soil samples are analyzed for nitrate, may account in part for the lack of correlation between apparent soil nitrate and crop behavior.…”
Section: Nitrate Toxicitysupporting
confidence: 85%
“…as non-accumulators. Kretschmer (1958), using a peaty muck soil of the Everglades, agreed in general with this classifi cation as he classed permanent pasture grasses and legumes as non-accumulators of nitrates. Hanway and Moldenhauer (1965), however, have reported that bromegrass did accumulate nitrate on an Ida soil in Iowa.…”
Section: Nitrate Toxicitymentioning
confidence: 57%